The clarity of the information regarding the bioeconomy: An analysis of the reports published by the organizations - Viorel Avram; Daniela Artemisa Calu; Valentin Florentin Dumitru; Tatiana Dănescu (Amfiteatru Economic Journal, 2019)
Bioeconomy is a material potential source of sustainable growth that calls for new approaches in research and innovation to bring about concrete improvements in Europe's social, economic and environmental wellfare. The purpose of our research is to evaluate the clarity of reports published by organizations. The assessment of the clarity of the published reports is done for both financial and non-financial information (containing elements related to bioeconomy). The steps of this research are: (i) the investigation of the clarity of the information included in the sustainability reports, and (ii) explanation of the atypical evolution of the clarity score, using the characteristics of the cultural dimensions of the home country. We analysed 77 reports published on the websites of 17 organizations in three environmentally-sensitive activity domains in 11 countries. Using content analysis, we determine an annual score of information clarity for each organization. The results of the research show that after switching to integrated reporting in 2013 the score of information clarity was improved for 65% of the companies. Eleven organizations have a degree of information clarity for the reports published in 2013 and 2016 better than for those published in 2010. We find five atypical cases for which the score of information clarity remains the same for all the three periods under investigation. These cases have been analyzed from the point of view of the cultural characteristics existing in the organization's home country. Through our research we provide feedback to organizations on how they can improve the clarity of their published reports.
Keywords: Q56; 330; bioeconomy; sustainability reporting; integrated reporting; clarity of information